Peritoneal dialysis manual : a guide for understanding the treatment - Krediet, Raymond T.; Struijk, Dirk G.; Esch, Sadie van 1979- (Basel Karger, 2018)
Peritoneal dialysis (PD) is a valid renal replacement therapy when incorporated in an overall integrated care programme for end-stage renal disease patients. Despite this fact, PD has not yet been established as a true long-term dialysis modality. This practical handbook offers sensible advice as well as detailed information on virtually all clinical and pathophysiological aspects of PD in a readily accessible format and explains the complexities of PD in a clear but still scientific and comprehensive way. Due to its handy size it fits in a white coat pocket of a nephrologist visiting a PD patient during rounds or in the outpatient ambulatory setting. Nephrologists, residents in nephrology and internal medicine, and all other health care workers - nurses, pharmacists, dieticians, intensivists, and medical students - involved with patients suffering from end-stage renal disease will find this book very helpful for understanding the scientific background of PD.
Keywords: DIÁLISIS PERITONEAL